Impressions of WSIS-2 in Tunis - Ndiaye, Oumy (Technical Centre for Agricultural and Rural Cooperation, 2006)
Oumy Ndiaye, head of CTA's Communication Channels and Services Department, attended the second World Summit on the Information Society (WSIS-2) held in Tunis, 16 18 November 2005. Here she gives some impressions of the meeting.